Copper(II) ion exchanged A1SBA-15: a versatile catalyst for intermolecular hydroamination of terminal alkynes with aromatic amines - Shanbhag, Ganapati V.; Joseph, Trissa; Halligudi, Shivaraj B. (Journal of Catalysis, 2007)
The hydroarnination reaction offers a very attractive route for the synthesis of alkylated amines and their derivatives with no byproduct formation. AISBA-15 was synthesized by isomorphous substitution of aluminum into the framework of SBA-15, which induces the Bronsted acid sites, and these were exchanged with metal ions such as Cu2+, Zn2+, and Pd2+. The catalysts were characterized by XRD, N-2-sOrption, SEM, TEM, acidity measurements by FT-IR pyridine adsorption, H-2-TPR, (27)AI MAS NMR, and Si-29 MAS NMR. Hydroamination of phenylacetylene (PhAc) with 2,4-xylidine has been used as a test reaction, which gave N-(1-phenylethylidene)-2,4-dimethylaniline with no byproduct formation. CuAlSBA-15 and CuAIMCM-41 showed around three times greater activity in hydroamination of PhAc compared with Cu-clay and Cu-beta, due to the moderate Lewis acidity of Cu2+ present in mesoporous supports. The performance of the CuAlSBA-15 was also determined with different alkynes and amines to evaluate the catalyst's general applicability in hydroamination reactions. (c) 2007 Elsevier Inc. All rights reserved.
Keywords: A1SBA-15; addition; alkyne; Amine; Copper catalyst; heterogeneous; hydroamination; ion exchange; Mesoporous